Schooling time decisions in closed and open economies - Carlotta Berti-Ceroni; Giorgio Bellettini; Giorgio Basevi (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1999)
We analyze a tree-period OLG model, where a consumption good is produced by means of skilled labor and an intermediate good. Human capital accumulation depends on the aggregate stock of human capital and on the fraction of time that children spend at school, which is decided by their parents. The remaining time is used as the only input in the production of the intermediate good. We compare schooling time decisions in countries where they are privately made and in countries where they are collectively set through compulsory education laws. We study the dynamic behavior of these economies and find that human capital accumulation will always be larger in the latter case. With international trade, private schooling decisions change according to the initial pattern of comparative advantage. Instead, the outcome of collective schooling decisions does not necessarily follow the pattern of comparative advantage.
Keywords: 330